2002
DOI: 10.1046/j.1420-9101.2002.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of wing pattern diversity in the Lycaenidae: mate discrimination by two recently diverged species

Abstract: Closely related species of lycaenid butterflies are determinable, in part, by subtle differences in wing pattern. We found that female wing patterns can act as an effective mate-recognition signal in some populations of two recently diverged species. In field experiments, we observed that males from a Lycaeides idas population and an alpine population of L. melissa preferentially initiate courtship with conspecific females. A morphometric study indicated that at least two wing pattern elements were important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 42 publications
3
117
1
Order By: Relevance
“…We hypothesize that the blue opsin gene duplication and the associated evolution of the 500·nm visual pigment may be causally linked to the radiation of this family that is famous for blue butterflies, including Nabokov's Blues (Tribe Polyommatini) (Nabokov, 1945). While cues from UV, LW and polarized light (Silberglied, 1984;Jiggins et al, 2001;Fordyce et al, 2002;Sweeney et al, 2003) have been recognized as important social signals in butterfly communication, our data suggest that blue cues in blue butterflies may provide an equally important signal for visual communication.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that the blue opsin gene duplication and the associated evolution of the 500·nm visual pigment may be causally linked to the radiation of this family that is famous for blue butterflies, including Nabokov's Blues (Tribe Polyommatini) (Nabokov, 1945). While cues from UV, LW and polarized light (Silberglied, 1984;Jiggins et al, 2001;Fordyce et al, 2002;Sweeney et al, 2003) have been recognized as important social signals in butterfly communication, our data suggest that blue cues in blue butterflies may provide an equally important signal for visual communication.…”
Section: Introductionmentioning
confidence: 99%
“…Mimetic butterflies have been used both in the identification of putative forest refugia (Brown 1979) where vicariant speciation might have occurred, as well as in studies of ecological speciation (Jiggins et al 2004a). Butterfly wing patterns are obvious phenotypic traits that show rapid evolution and play a role in reproductive isolation (Vane-Wright 1978;Jiggins et al 2001;Lukhtanov et al 2005), being used in sexual signaling and mate choice (Stride 1957(Stride , 1958Brower 1959;Lederhouse and Scriber 1996;Deering and Scriber 2002;Fordyce et al 2002), as well as in predator defence. A number of butterflies in Neotropical forests are unpalatable to predators and bear warning color patterns, and sympatric species tend to converge in pattern through mimicry to facilitate predator recognition (Mü ller 1879).…”
mentioning
confidence: 99%
“…In support of the deflection hypothesis, it has been demonstrated that the posterior hind wing tornus is more noticeable yet structurally weaker than the surrounding areas in a sample of African species (DeVries 2002(DeVries , 2003 Field experiments and observations demonstrated that ventral oceli play a role in mate selection. Choice trials showed that male Lycaeides idas (Linnaeus, 1761) (Lycaenidae) selected females based on the size of their ventral hind wing aurorae and spots (Fordyce et al 2002), and male and female Bicyclus anynana show a seasonal preference for ocelus size (Prudic et al 2011). During courtship, male Pierella astyoche hover by decoupling forewing from hind wing movement, and clearly display the large hind wing white spots to the potential mate (CMP pers.…”
Section: Discussionmentioning
confidence: 99%